Enhancing exploratory analysis by summarizing spatiotemporal events across multiple levels of detail - Silva, Ricardo Almeida (2016)
There are many spatiotemporal events with high levels of detail (LoDs) being collected in many phenomena. The LoD of analysis plays a crucial role in the user’s perception of phenomena. From one LoD to another, some patterns can be easily perceived or different patterns may be detected. Standard practices work on a single LoD driven by the user in spite of the fact that there is no exclusive LoD to study a phenom- enon. Our proposal aims to support users in carrying the inspection and comparison tasks of a phenomenon across multiple LoDs, without having to look at raw data, and to handle the spatiotemporal complexity. This paper presents a framework to build abstracts at different LoDs where five types of abstracts are proposed. The framework makes no assumption about the phenomenon, the analytical task and the phenomenon’s LoDs. The SUITE’s prototype implements the proposed framework allowing users to inspect abstracts across multiple LoDs simultaneously, helping to understand in what LoDs the phenomenon perception distinguishes itself or in what LoDs “interesting patterns” emerge.